KONSELING INDIVIDUAL OLEH GURU BK BAGI PESERTA DIDIK MEMBOLOS DI SMPN 3 SUNGAI RAYA - Nur Halimah; Indri Astuti; Luhur Wicaksono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractResearchers want to know the implementation of individual counseling by guidance and counseling teachers for truant learners. Research problem is "how is the implementation of individual counseling by guidance and counseling teachers to truant students at SMP Negeri 3 Sungai Raya”. The purpose of study was to obtain information and describe the implementation of individual counseling by guidance and counseling teachers to truant students at SMP Negeri 3 Sungai Raya. Method used was descriptive quantitative approach in form survey. Population research was 23 students and 2 teachers guidance and counseling. Data collection technique used was indirect communication of questionnaires and documentation studies. Data analysis technique used was percentage. Overall the implementation of individual counseling by guidance and counseling teachers to truant students obtained a 59% good enough category. The stage defining the problem of individual counseling by the guidance and counseling teacher to truant students obtained a 56% good enough category. The work phase of individual counseling by guidance and counseling teachers for truant students was obtained by 60% good enough category. The stage of individual counseling by the guidance and counseling teacher to truant students obtained a 62% good enough category. Keywords: Individual Counseling, Truant